Measuring and analyzing the impact of government and private bank credit on non-oil GDP in Iraq for the period (2004-2019) - Mihi, Shaimaa; Obeyd, Salah (Humanities Journal of University of Zakho, 2022)
This study aims to measure the impact of public and private bank credit on the non-oil GDP in Iraq for the period (2004-2019). The study relied on analyzing the effect of a group of variables most affecting the dependent variable using advanced statistical methods. The study relied mainly on the Ordinary Least Squares (OLS) method in estimating the effect of bank credit variables on non-oil GDP, as well as the standard model to confirm the absence of the autocorrelation problem according to the (LM) test, and the absence of the estimated model from the problem of heterogeneity according to the (ARCH) test. The results of the study were identical to the alternative hypothesis, which states that there is a significant and weak effect of the credit of private banks on the non-oil GDP (NOGDP) with no significant effect of the credit of public banks on the non-oil GDP. This is due to the fact that the Iraqi economy is a rentier economy that depends on oil as a major source for the state, and to other factors that affect non-oil output, the most important of which is the security and political issues. The study suggests the necessity of activating the role of bank credit in the production process by addressing the structural imbalances in the Iraqi economy.